2020
DOI: 10.5944/ried.24.1.27960
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de las TIC en el rendimiento escolar de estudiantes vulnerables

Abstract: El sistema educativo contemporáneo está influenciado por los movimientos migratorios y el desarrollo de las Tecnologías de la Información y la Comunicación (TIC). Este trabajo analiza la influencia de las TIC en el rendimiento escolar de estudiantes vulnerables. Para ello, se estudian las relaciones del rendimiento escolar con el país de origen del estudiante, la conexión a Internet en el hogar y el uso diario de dispositivos digitales. Apoyado en la metodología de investigación en educación comparada, se cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
2
8
0
7
Order By: Relevance
“…Regarding the impact of the frequency of use of ICT on grades, the results presented confirm what was indicated by [ 26 , 31 ], who found a statistically significant relationship between the frequency of use of the video console and low academic grades. Therefore, it is concluded that a greater number of hours of play is positively and significantly related to a low academic performance.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding the impact of the frequency of use of ICT on grades, the results presented confirm what was indicated by [ 26 , 31 ], who found a statistically significant relationship between the frequency of use of the video console and low academic grades. Therefore, it is concluded that a greater number of hours of play is positively and significantly related to a low academic performance.…”
Section: Discussionsupporting
confidence: 86%
“…As for the console, it was found that the following factors predict the negative impact of console on academic performance: frequency of use of console coinciding with [26], who determined that high frequency of videogames is related to poor academic performance; abandonment of academic tasks due to being playing for longer; need to invest more and more time online; staying up late using console; study time spent on the Internet coinciding with [25,31], who highlight that students who spend more time playing videogames present worse academic performance; anger when play is interrupted; age; and stress. This result implies the rejection of H2, since it includes age, stress and staying up late as predictors of academic decline.…”
Section: Discussionmentioning
confidence: 99%
“…The shift to remote training was initiated by the closure of classrooms, what deprived both students and instructors from diverse rights and benefits. On the one hand, it had a negative impact on the inclusion process in Higher Education, understood as the ongoing and transformative process of improving education systems to meet all learners' needs, especially those in low-achieving students or with low-income families [24][25][26]. On the other hand, the change to remote teaching has implied a step forward to the so-called ubiquitous learning [27,28].…”
Section: Description Of the Studymentioning
confidence: 99%
“…The COVID-19 pandemic re ected the pro les of students who do not have access to the Internet at home and presented di culty in accessing a virtual education, the importance of the Internet connection at home and the daily use of digital devices is perceived (Hurwitz & Schmitt, 2020;Vidal, 2021). However, the literature identi es other pro les of students who consider they have insu cient technological skills, di culties to effectively implement the instructions of the educational center and di culty in catching up with the constant changes in ICT (Rodicio García, Ríos-de-Deus, Mosquera-González & Abilleira, 2020)…”
Section: Educational Exclusion Pro Lesmentioning
confidence: 99%